Chapter 8: retrospective criminal laws and double jeopardy - Kamarudin, Abdul Rani; Masum, Ahmad; Ali Mohamed, Ashgar Ali; Ahmad, Muhamad Hassan; Arowosaiye, Yusuf Ibrahim (LexisNexis, 2022)
No person shall be punished for an act or omission which was not punishable by law when it was done or made, and no person shall suffer greater punishment for an offence than was prescribed by law at the time it was committed. A person who has been acquitted or convicted of an offence shall not be tried again for the same offence twice.